Parents-reported nutrition and feeding difficulties in infants with congenital diaphragmatic hernia after hospital discharge - Leyens, Judith; Bo, Bartolomeo; Heydweiller, Andreas; Schaible, Thomas; Boettcher, Michael; Schroeder, Lukas; Müller, Andreas; Kipfmüller, Florian (Early human development, 2024)
Purpose - Congenital diaphragmatic hernia (CDH) affects 1 in 3000-5000 newborns. In survivors, long-term complications include gastroesophageal reflux (GER), feeding difficulties, and failure to thrive. Data from the parents' perspective remain scarce. This study aims to report the prevalence and impact of feeding difficulties on CDH families after discharge. - Methods - National web-based survey amongst families with CDH infants in 2021. - Results - Caregivers of 112 CDH survivors participated. The baseline characteristics were representative with 54 % male, 83 % left-sided CDH, prenatal diagnosis in 83 %, and 34 % requiring extracorporeal membrane oxygenation. Most infants (81 %) were discharged within three months, with 62 % feeding by mouth, and 30 % requiring a feeding tube. Persisting feeding difficulties were experienced by 73 %, GER being the most common (66 %), followed by insufficient weight gain (64 %). After discharge, 41 % received medical support for failure to thrive. The primary-care pediatrician was consulted most frequently for information (61 %) and treatment of feeding difficulties (74 %). Therapeutic success was reported in 64 %. A cessation of symptoms was achieved in 89 % within three years. - Conclusion - The majority of CDH infants had persistent feeding difficulties. This survey highlights the impact surrounding feeding problems on CDH families. Further studies and support systems are needed to raise the quality of life in CDH infants and their families.
Gesehen am 09.12.2024